Analysis Of Geographic Information System Using SDLC (System Development Life Cycle) - Agustina A N; Ariani F (International Conference on Engineering and Technology Development (ICETD), 2017)
Information requirements in the present belongs to the essential needs, because an update is support in an activity. Knowing the information somewhere is important for each of them in order to support efficiency in terms of time and cost. Google Maps is a pointer system location or mapping information online the most popular today. Google Maps is not only available in the form of applications, but also web based. Nowadays more and more emerging applications apps are designed to facilitate employment or human activity, especially in the android application that uses Google maps. Thus many persons are racing to create a Geographic Information System application to determine a location and makes it easy somewhere that can also be used to promote an area that uses the application. With the strategy of information systems and information technology right in running GIS application development then the goal will be achieved with the desired appropriate.